Clocks Underneath: The Role of Peripheral Clocks in the Timing of Female Reproductive Physiology - Sellix, Michael T. (Frontiers in Endocrinology, 2013)
The central circadian pacemaker in the suprachiasmatic nucleus (SCN) is a critical component of the neuroendocrine circuit controlling gonadotropin secretion from the pituitary gland. The SCN conveys photic information to hypothalamic targets including the gonadotropin releasing hormone (GnRH) neurons. Many of these target cells are also cell autonomous clocks. It has been suggested that, rather then being singularly driven by the SCN, the timing of gonadotropin secretion depends on the activity of multiple hypothalamic oscillators. While this view provides a novel twist to an old story, it does little to diminish the central role of rhythmic hypothalamic output in this system. It is now clear that the pituitary, ovary, uterus and oviduct have functional molecular clocks. Evidence supports the notion that the clocks in these tissues contribute to the timing of events in reproductive physiology. The goal of this review is to highlight the current evidence for molecular clock function in the peripheral components of the female hypothalamo-pituitary-gonadal (HPG) axis as it relates to the timing of gonadotropin secretion, ovulation and parturition.